DIGITALISASI KEUANGAN UKM (Studi Kasus CV. Madu Mekar Purwakarta) - Pandena Kicky Basuki Putri; Darmawan Yudhanegara; Rizki Fadilah (Jurnal Riset Entrepreneurship, 2021)
The Small and Medium Enterprises is plays an active role in efforts to rapidly increase business operations. The effort he does is to use technological devices to simplify the operational process in finance. This study aims to compare manual calculations with existing technology. The use of technology has a speed of completing financial statements and income statements of only 20 minutes, with an internet credit quota of IDR. 35,000 per three months. Meanwhile, manual counting use requires a stationery fee of IDR. 75,000 per three months at a reporting rate of 3 hours.